On the Nature of Organs and Organ Systems – A Chapter in the History and Philosophy of Biology - Minelli, Alessandro (Frontiers in Ecology and Evolution, 2021)
Contrasting definitions of organs based either on function or on strictly morphological criteria are the legacy of a tradition starting with Aristotle. This floating characterization of organs in terms of both form and function extends also to organ systems. The first section of this review outlines the notions of organ and body part as defined, explicitly or implicitly, in representative works of nineteenth century’s comparative morphology. The lack of a clear distinction between the two notions led to problems in Owen’s approach to the comparative method (definition of homologue vs. nature of the vertebrate archetype) and to a paradoxical formulation, by Anton Dohrn, of the principle of functional change. Starting from the second half of the twentieeth century, with the extensive use of morphological data in phylogenetic analyses, both terms – organ and body part – have been largely set aside, to leave room for a comparison between variously characterized attributes (character states) of the taxa to be compared. Functionally defined organ are occasionally co-extensive with morphologically defined body parts, nevertheless a clear distinction between the former and the latter is a necessary prerequisite to a study of their evolution: in the last section of this article, this issue is discussed the example of hermaphroditism and gonad structure and functions